2014
DOI: 10.4172/2167-1079.1000170
|View full text |Cite
|
Sign up to set email alerts
|

Focused Antenatal Care Service Utilization and Associated Factors in Dejen and Aneded Districts, Northwest Ethiopia

Abstract: Background: Focused antenatal care considers every pregnant woman at high risk for developing pregnancyrelated complications. Hence, all pregnant women should receive at least four antenatal visits to early identify the complications and intervene accordingly. Therefore, this study attempted to assess focused antenatal care service utilization and associated factors among mothers who gave birth in the last 2 years prior to the study in Dejen and Aneded districts, Northwest Ethiopia. Methods:A community-based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…Marital status offered significant protection for ANC attendance, as unmarried women had reduced odds of making at least one ANC visit. This finding is consistent with many other studies conducted in Ghana (8,31,40,41), and Kenya (38), but contradicts the study results from Ethiopia (42,43). The possible reason for this finding could be attributed to society’s values on marriage and pregnancy.…”
Section: Discussionsupporting
confidence: 87%
“…Marital status offered significant protection for ANC attendance, as unmarried women had reduced odds of making at least one ANC visit. This finding is consistent with many other studies conducted in Ghana (8,31,40,41), and Kenya (38), but contradicts the study results from Ethiopia (42,43). The possible reason for this finding could be attributed to society’s values on marriage and pregnancy.…”
Section: Discussionsupporting
confidence: 87%
“…Findings from Northwest Ethiopia revealed that the traveling time of respondents was significantly associated with the utilization of ANC service. Pregnant mothers who traveled less than one hour were eight times more likely to attend antenatal care than those who travel more than one hour [ 18 ]. A study done in Nepal mentioned cultural practices, shyness to be seen by men providers, and attitudes of health care providers to have influenced women´s decisions not to seek care [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also consistent with another similar study conducted in 2009 in Yem special Woreda, southwestern Ethiopia, where 28.5% of women had FANC services during their last pregnancy, while, higher than the studies done in Northeast, Northwest, and southern Ethiopia. [20][21][22] This variation may be due to differences in time of study and settings.…”
Section: Discussionmentioning
confidence: 99%